An updated assessment of the seabird populations breeding at Príncipe and Tinhosas. (2nd January 2018) - Bollen, An; Matilde, Estrela; Barros, Nuno
Abstract : The Príncipe Autonomous Region is recognised as a marine biodiversity hotspot, although little is known about the status of its marine fauna. It holds most breeding seabirds of the tropical eastern Atlantic Ocean. Based on anecdotal accounts of increased fishing and seabird harvesting, regular monitoring of seabird populations is considered a priority. Therefore, a survey of Príncipe's seabird colonies was conducted in 2017. The results revealed that the more accessible seabird colonies have disappeared. Around Príncipe, Boné de Joquei is the present main stronghold for Brown Boobies Sula leucogaster and White-tailed Tropicbirds Phaethon lepturus . The Tinhosas islands hold an estimated 300 000 seabirds, predominantly Sooty Terns Onychoprion fuscatus, but also Brown Boobies, Black Noddies Anous minutus and Brown Noddies Anous stolidus . Long-term multi-annual monitoring is needed to understand the breeding phenology of each species and to better assess population trends. Ensuring a protective status for both Tinhosas and the seabirds under national legislation is a key priority for future conservation policy in São Tomé and Príncipe.